AN INTEGRATED HOLISTIC APPROACH TO IMPROVING THE THEORY OF ENVIRONMENTAL AND SOCIAL IMPACT ASSESSMENT (ESIA) FOR URBAN PLANNING DEVELOPMENT IN MALAYSIA - Loh Yong Seng; Siti Isma Hani Ismail; Shanker Kumar Sinnakaudan; Zulfairul Zakaria; Mohd Fairuz Bachok, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
All environmental legislation, laws, and regulations must be followed by the construction industry in Malaysia. Before starting a new project, the relevant project must undergo two major assessments namely the Environment Impact Assessment (EIA) and the Social Impact Assessment (SIA) (SIA). The goal of this study is to evaluate the theoretical framework of EIA and SIA current practice/implementation for construction project approval by Malaysian authorities and recommend suitable holistic approach in ESIA theoretical framework for approving system. The collected data from 175 respondents via structured questionnaire survey and analyzed using SPSS Software, are then used to create and recommend an appropriate ESIA framework for adaptation. Overall, the study aims to improve Malaysia's approval system by recommending an integrated holistic approach to project approval based on ESIA theoretical framework, in accordance with environmental legislation, laws, and regulations. Besides, the framework will provide information, guidance and materials in this volume than able to assist EIA and SIA practitioners in these countries to design and implement processes that correspond to international standards of good practice.